(untitled) (Research, Society and Development, 2020)
The purpose of this article is to propose a reflection on the importance of the normative adequacy of a company in the adoption of Compliance Programs, with a view to obtaining benefits for management, especially in relation to the impacts of taxes on revenues and risk reduction through the tax avoidance, the clearest objective of tax planning. Through the bibliographic review method, we confer the importance of this study to proactive business practices, whose results have been propositional for business administration. The results obtained with this research are in the positive and expected field of prospecting for facilities for companies, which was observed through the adoption of Compliance programs automatically reverted to benefits for the company, reflecting, therefore, in management and its relationship with its employees and stakeholders, who indirectly enjoy the credibility of the planned company. Through this study it is concluded that the companies that adopt Tax Compliance have less costs, higher profits, greater labor speed and a differentiated results range, which makes them true management models, consolidating their brand as a reference in credibility. Compliance, without any doubt, as highlighted in the results of this research, has been identified as the most appropriate tool for achieving the objectives of good tax planning and these benefits also achieve results in reducing risks for the company, reducing or eliminating your extra expenses and tax impacts on management.